2012
DOI: 10.2175/106143012x13354606450924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long Exposure to Low Temperatures on Nitrifying Biofilm and Biomass in Wastewater Treatment

Abstract: BSTRACT: Attached growth biological treatment systems are a promising solution to ammonia removal in cold-temperature climates. Environmental scanning electron microscopy (ESEM) and confocal laser scanning microscopy in combination witb fluorescent in situ hybridization (EISH) was used to investigate the effects of 4 months of exposure to 4 "C on nitrifying biofiim and biomass. These molecular and microscopic methods were modified to minimize loss of mass and distortion of in situ perspectives. Environmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…1b), indicating that soil moisture is not the main factor causing differences in N 2 O emission between treatments. It is known that low temperature mainly influences microbial metabolic rates (Hulsen et al 2016), which leads to the deterioration of nitrification (Chen et al 2018;Delatolla et al 2012;Hoang et al 2014). In addition, low temperatures exert an influence on the amount of nitrifying bacteria (Siripong and Rittmann 2007).…”
Section: N 2 O Fluxmentioning
confidence: 99%
“…1b), indicating that soil moisture is not the main factor causing differences in N 2 O emission between treatments. It is known that low temperature mainly influences microbial metabolic rates (Hulsen et al 2016), which leads to the deterioration of nitrification (Chen et al 2018;Delatolla et al 2012;Hoang et al 2014). In addition, low temperatures exert an influence on the amount of nitrifying bacteria (Siripong and Rittmann 2007).…”
Section: N 2 O Fluxmentioning
confidence: 99%
“…In our experiments, the biofilms in 1st stage dropped off and were replaced during 20-25 days while the biofilms in 2nd stage and 3rd were maintained well up to 40-60 days. It was reported that attrition rather than sloughing is the prevailing biomass loss mechanism [32]. According to the loss amount of biomass in basin, the sludge age was roughly 28-35 days.…”
Section: Effect Of Influent Concentration On Bodmentioning
confidence: 99%
“…It frequently dictates footprint and energy use in biological wastewater treatment (McCarty et al ., 2011; Liu et al ., 2018), and is also a common candidate for process disruption (Siripong and Rittman, 2007), owing to its dependence on two interdependent groups of slow-growing autotrophs: ammonia oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB). AOB maintain a stable population during long-term low-temperature periods, even when the nitrification process fails (Delatolla et al ., 2012; Johnston et al ., 2019). AOB were also shown to be more resistant and resilient than NOB under a sustained operational disturbance where the organic loading to replicate bioreactors was changed (Santillan et al .…”
Section: Introductionmentioning
confidence: 99%